70th anniversary of the Pharmaceutical Faculty of Siberian State Medical University - V. S. Chuchalin (Бюллетень сибирской медицины, 2011)
The paper is devoted to the history of Pharmaceutical Faculty of Siberian State Medical University (Tomsk Medical Institute). The role of В статье отмечается роль deans, teachers, and scientists in establishment of the department is mentioned. Scientific researches performed by faculties and laboratories are characterized. The material presented reflects the main promises in development of the departmentand enhancement of its infrastructure.